Patriotic name bias and stock returns - Benos, E. (2016)
Companies whose names contain the words "America(n)" or "USA" earn positive abnormal returns of about 6% per annum during World War II, the Korean War, and the War on Terrorism. These abnormal returns are not realized immediately upon the outbreak of each of the wars but are accumulated gradually during wartime. Given that no such effect is observed for the Vietnam War, we hypothesize that major, victorious wars arouse investors' patriotic feelings and cause them to gradually and perhaps subconsciously gravitate toward stocks whose name has a patriotic flavor.